Por uma Terapia Ocupacional não opressora: percepções e experiências de terapeutas ocupacionais sobre papéis sociais de gênero e suas práticas profissionais - Gomes, Fernanda Desuó (Universidade Federal de São Carlos, 2021)
This research is quanti-qualitative and has as its theme the conceptions of gender in the context of practices in Occupational Therapy from a decolonial feminist perspective. It aimed to analyze the perceptions of occupational therapists about gender and their experiences about social roles based on sex/gender during their professional practices. For data collection, a form with multiple-choice questions and space for comments and descriptive reports was produced. The research had the participation of occupational therapists who have been working for at least two years in any region of Brazil and in different areas of Occupational Therapy, in order to identify the possible reproduction in professional practices of hegemonic power systems (status quo) and norms in relation to social roles, as well as possible discussions and reflections triggered by this theme. The presentation and analysis of quantitative data was performed through tabulations in the Microsoft Excel® program, while the answers arising from the open questions were grouped according to associated themes: a) concepts about gender; b) how gender norms and roles are represented in Occupational Therapy practices and c) reflections by professionals in relation to this theme. The results were discussed under the light of the theoretical references of Occupational Therapy and a decolonial feminist perspective, pointing to the urgency of deepening gender issues in the field of Occupational Therapy in order to contribute to the production of transformative knowledge and practices, centred on social rights and in the plurality and diversity of existences and daily lives.
For a non-oppressive Occupational Therapy: occupational therapists' perceptions and experiences about social gender roles and their professional practices
Para una Terapia Ocupacional no oppresiva: percepciones y experiencias de los terapeutas ocupacionales sobre los roles sociales de género y sus prácticas profesionales
Keywords: Estudos de Gênero; Papel de Gênero; Terapia Ocupacional; Prática Profissional; OUTROS::ESTUDOS SOCIAIS